A Monitoring System for Integrated Management of IoT-based Home Network - Changsu Ryu; Chang-Wu Hur (Institute of Advanced Engineering and Science, 2016)
Recently, the society is rapidly becoming highly integrated with the convergence of smart devices, SNS, big data, cloud, and IoT. This phenomenon is being spread more swiftly based on the wired and wireless communication infrastructure provided to most homes, as terminal devices for communication have more various functions and are being supplied to homes through a multi-vendor system and as several terminal devices are installed in each home to provide services. Particularly, various IoT terminal devices and services are being introduced to facilitate functions such as home crime prevention, gas valve control, control of electric apparatus and temperature-humidity sensors, and door control based on facial recognition, and integrated IoT-based management monitoring is required for TVs, washing machines, refrigerators, etc. Hence, in this study, a monitoring system for integrated home network management and data collection management, which solves problems of existing home network systems by connecting API Adaptor connection technology, message technology for integrated management of universal communications terminal devices and IoT devices, and data modelling technology to individual network platforms, was proposed.